2012
DOI: 10.1103/physrevb.86.165408
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of coupled plasmon polariton wave packets excited at a subwavelength slit in optically thin metal films

Abstract: We study by numerical simulations the excitation and propagation dynamics of coupled surface plasmon polariton (SPP) wave packets (WPs) in optically thin Ag films and a bulk Ag/vacuum interface under the illumination of a subwavelength slit by 400 nm continuous wave (cw) and femtosecond pulsed light. The generated surface fields include contributions from both SPPs and quasi-cylindrical waves, which dominate in different regimes. We explore aspects of the coupled SPP modes in Ag thin films, including symmetry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…al. [267], positioning any probe, such as an AFM tip, in the vicinity of the slit stablishes standing wave oscillations between the tip and the slit, leading to a series of minima/maxima that convolve with those of the interference envelope. Having said that, measurements carried out by Verhagen et.…”
Section: Simulations Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [267], positioning any probe, such as an AFM tip, in the vicinity of the slit stablishes standing wave oscillations between the tip and the slit, leading to a series of minima/maxima that convolve with those of the interference envelope. Having said that, measurements carried out by Verhagen et.…”
Section: Simulations Results and Discussionmentioning
confidence: 99%
“…al. [267] modelled a free standing optically thin silver film in vacuum, where authors try to explain their findings in terms of long range SPPs, SPP Wave Packets and Quasi Cylindrical Waves (QCW) … etc. Prior to that, Verhagen et.…”
Section: Travelling Spps With Non-travelling Interference Envelopementioning
confidence: 99%
“…New adsorbate-induced electronic states arise at the interface [301,302]. Hence, the remarkable plasmon broadening is due to new channels for decay into e-h pairs at the K/Ag interface.…”
Section: Cid Of the Sp In The K-modified Ag Filmmentioning
confidence: 98%
“…Moreover, most of previous studies have employed the surface normal illumination of the planar plasmonic lens, but only a few have considered the more general case of the focusing properties for off‐normal incidence . The off‐normal incidence may be required by the experimental geometry, such as by the restricted sample access as in a PEEM, or to improve the coupling efficiency . Indeed, recently Lemke et al reported an ITR‐PEEM study for offnormal incident excitation field onto elliptical and Fresnel lens structures, which were used to focus SPP‐WPs at Au/air interface, though no design principles for the optimal focusing were given .…”
mentioning
confidence: 99%